Contributions to the Flora of Peary Land, North Greenland. - Fredskild, Bent (Meddelelser om Grønland, 1966)
This paper can be considered as an addition to K. HOLMEN: The vascular plants of Peary Land, North Greenland. Medel. o. Grønl. 121, , 9. It deals with the collections made by the author in 1963. 7 species new to North Greenland were found: Carex saxatilis, Fettuca vivipara, Hippuris vulgaris, Juncus castaneus, Pedicularis capitata, Ranunculus triochophyllus var. eradicatus, and Saxifraga tricuspidata. Some new localities were visited (loc. Nos 97- 101 ). In the list of species new records besides some ecological and phenoloi; ical additions are also given. Finally the paper gives the determinations of the material brought home to Copenhagen from loc. Nos 47c, 81 and 102- 106 by various collectors since 1957. In this material was also found another species new to North Greenland, Carex glacialis.